Difference in Mono-O-Glucosylation of Ras Subtype GTPases Between Toxin A and Toxin B From Clostridioides difficile Strain 10463 and Lethal Toxin From Clostridium sordellii Strain 6018 - Genth, Harald; Junemann, Johannes; Lämmerhirt, Chantal M.; Lücke, Arlen-Celina; Schelle, Ilona; Just, Ingo; Gerhard, Ralf; Pich, Andreas (Frontiers in Microbiology, 2018)
C. difficile toxin A (TcdA) and Toxin B (TcdB) trigger inflammasome activation with caspase-1 activation in cultured cells, which in turn induce the release of IL-6, IFN-γ, and IL-8. Release of these proinflammatory responses is positively regulated by Ras-GTPases, which leads to the hypothesis that Ras glucosylation by glucosylating toxins results in (at least) reduced proinflammatory responses. Against this background, data on toxin-catalyzed Ras glucosylation are required to estimate of pro-inflammatory effect of the glucosylating toxins. In this study, a quantitative evaluation of the GTPase substrate profiles glucosylated in human colonic (Caco-2) cells treated with either TcdA, TcdB, or the related C. sordellii lethal toxin (TcsL) was performed using multiple reaction monitoring (MRM) mass spectrometry. (H/K/N)Ras are presented to be glucosylated by TcsL and TcdA but by neither TcdB isoform tested. Furthermore, the glucosylation of (H/K/N)Ras was detected in TcdA-(not TcdB)-treated cells, as analyzed exploiting immunoblot analysis using the Ras glucosylation-sensitive 27H5 antibody. Furthermore, [14C]glucosylation of substrate GTPase was found to be increased in a cell-free system complemented with Caco-2 lysates. Under these conditions, (H/K/N)Ras glucosylation by TcdA was detected. In contrast, TcdB-catalyzed (H/K/N)Ras glucosylation was detected by neither MRM analysis, immunoblot analysis nor [14C]glucosylation in a cell-free system. The observation that TcdA (not TcdB) glucosylates Ras subtype GTPases correlates with the fact that TcdB (not TcdA) is primarily responsible for inflammatory responses in CDI. Finally, TcsL more efficaciously glucosylated Ras subtype GTPase as compared with TcdA, reinforcing the paradigm that TcsL is the prototype of a Ras glucosylating toxin.